Stress in Patients With (Un)ruptured Intracranial Aneurysms vs Population-Based Controls. Issue 5 (17th April 2018) - de Wilde, Arno; Greebe, Paut; Rinkel, Gabriël J E; Algra, Ale
Abstract: BACKGROUND: Stress is associated with increased risk of stroke and might predispose to presence and rupture of intracranial aneurysms. OBJECTIVE: To study the association of recent and lifelong stress with unruptured intracranial aneurysm (UIA) and aneurysmal subarachnoid hemorrhage (ASAH). METHODS: In 227 UIA patients (mean age 61 ± 11 yr), 490 ASAH patients (59 ± 11 yr), and 775 controls (51 ± 15 yr) who were randomly retrieved from the general population, we assessed occurrence of major life events and perceived stress during the preceding 12 mo and the entire life. With multivariable logistic regression analysis, we calculated odds ratios (ORs) with 95% confidence intervals (95% CIs) for 4 categories of life events (financial-related, work-related, children-related, and death of family members) and for periods of perceived stress at home and at work (never vs sometimes, often, or always). We adjusted for sex, age, alcohol consumption, smoking, and hypertension. RESULTS: The 4 categories of life events and perceived stress at work had ORs ranging from 0.4 to 1.7, of which financial stress for UIA was statistically significant (95% CI: 1.1-2.5). ORs for chronic perceived stress at home in the previous year were 4.3 (95% CI: 1.8-10.3) for UIA and 2.5 (1.2-5.5) for ASAH, and for lifelong exposure 5.7 (2.2-14.5) for UIA and 3.0 (1.3-7.0) for ASAH. CONCLUSION: For some components of stress, there may be a relation with UIA and ASAH. The mechanisms underlying this relation should be unraveled; strategies to improve coping with stress may reduce the risk of rupture in patients with unruptured aneurysms.